2023
DOI: 10.1123/iscj.2021-0045
|View full text |Cite
|
Sign up to set email alerts
|

Engaging in Paradigmatic Dialogue: A Bibliometric Analysis of Coaching Scholarship From 1970 to 2020

Abstract: Coaching scholarship (CS) sits at the intersection of multiple paradigms and disciplines. Despite the eclectic nature of the field, most scholars operate only within their preferred paradigm, which limits how coaching is conceptualized and practiced. To address this limitation, we used the dialectic stance to analyze bibliometric records of CS produced between 1970 and 2020 from both an interpretivist and poststructuralist perspective. Using Web of Science, we identified 2,522 coaching articles and organized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…and (c) What methodologies and data collection methods were used? These questions align with previous reviews of coaching literature (e.g., Campbell et al, 2022;Gilbert & Trudel, 2004) and coaching-focused scoping reviews (e.g., Bentzen et al, 2021). It is also a way to inform stakeholders (Levac et al, 2010) of ways to advance coaching science in this journal.…”
supporting
confidence: 69%
“…and (c) What methodologies and data collection methods were used? These questions align with previous reviews of coaching literature (e.g., Campbell et al, 2022;Gilbert & Trudel, 2004) and coaching-focused scoping reviews (e.g., Bentzen et al, 2021). It is also a way to inform stakeholders (Levac et al, 2010) of ways to advance coaching science in this journal.…”
supporting
confidence: 69%
“…16 To date, research studies utilizing a CBPR orientation are scarce within the coaching and sport for development literature, and a large number of studies focus on outcomes associated with trainings for coaches yet lack an emphasis on the processes underlying training development. [17][18][19][20] In a recent review of mental health awareness programs, Breslin and colleagues 17 identified five studies on mental health awareness interventions in sport (e.g. help-seeking, knowledge of disorders, and literacy) implemented with coaches.…”
Section: Community-based Participatory Researchmentioning
confidence: 99%
“…As such, opportunities exist to advance the coaching literature using different research paradigms and innovations to improve coach education and training. 18 For this study, our work was grounded in the CBPR conceptual model outlined by Wallerstein et al 13 The contexts guiding our work are described in our literature review (e.g. the importance of the health issue, social and structural changes due in part to COVID-19, policy governance over coach education and training in the US, and a high level of readiness reported by coaches/needs of student-athletes).…”
Section: Community-based Participatory Researchmentioning
confidence: 99%
See 1 more Smart Citation